Pengaruh Tenaga Kerja Terhadap Pendapatan UMKM, Modal Sendiri, dan Kredit Usaha Rakyat (Studi Kasus di Kecamatan Sekupang Kota Batam) - Kartika Sari; Hikmah Hikmah (eCo-Buss, 2024)
This study aims to ascertain the effects of employment, capital, and private enterprise on the revenue of MSMEs in Batam City. Quantitative procedures are employed to carry out this research since the research data is presented as numbers and is analyzed using statistics. The total number of MSMEs in Sekupang Regency is the study population, while 286 MSMEs in Sekupang Regency are used as research samples. The Unknown Populations Approach method was used to calculate the number of samples in the study population while selecting the sample population for this study. The t test's findings suggest that Batam City's MSME income is favorably influenced by own capital (X1) and KUR, while business income in Batam City is positively influenced by KUR (X2). While the number of employees is only statistically significant, it has a positive effect on the profits of SMEs in Batam City. While the quantity of employees is only statistically significant, it has a positive effect on the financial performance of SMEs in Batam City. However, it can be deduced from the f test results that own capital, labor, and individual company loans all concurrently have a significant and beneficial effect on MSME revenue in Batam City.